2019
DOI: 10.4254/wjh.v11.i6.522
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors increase the severity of hepatic encephalopathy in cirrhotic patients

Abstract: BACKGROUND Liver cirrhosis is the late stage of hepatic fibrosis and is characterized by portal hypertension that can clinically lead to decompensation in the form of ascites, esophageal/gastric varices or encephalopathy. The most common sequelae associated with liver cirrhosis are neurologic and neuropsychiatric impairments labeled as hepatic encephalopathy (HE). Well established triggers for HE include infection, gastrointestinal bleeding, constipation, and medications. Alterations to the gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…PPIs may affect renal function by damaging the glomerular interstitium and increasing the severity of hepatic encephalopathy or the risk of spontaneous bacterial peritonitis in liver cirrhosis patients 17‐19 . Therefore, to clarify the association between PPI and mortality, we also conducted subgroup analyses in patients with liver disease and renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…PPIs may affect renal function by damaging the glomerular interstitium and increasing the severity of hepatic encephalopathy or the risk of spontaneous bacterial peritonitis in liver cirrhosis patients 17‐19 . Therefore, to clarify the association between PPI and mortality, we also conducted subgroup analyses in patients with liver disease and renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…78 Furthermore, use of proton pump inhibitors (PPIs), which promotes small intestinal bacterial overgrowth, 87 is a risk factor for spontaneous bacterial peritonitis, more severe hepatic encephalopathy, and greater mortality. 88,89 Llorente et al 90 demonstrated that ethanol-fed mice treated with PPIs had overgrowth and increased gut translocation of Enterococcus spp, whereas human patients with ALD who used PPIs also had enrichment of Enterococcus spp in their feces.…”
Section: Alcohol-induced Liver Diseasementioning
confidence: 99%
“…150 HE is a serious complication of ESLD characterized by neurocognitive impairments, including confusion, lethargy, incoherent speech, sleep disturbances, and eventually coma. 88 The pathogenic mechanisms of HE are incompletely understood but appear to involve intestinal dysbiosis, increased production of ammonia by human cells and microbes, and systemic inflammation. 148,151,152 Kang et al 151 found that germ-free mice with liver fibrosis have lower serum levels of ammonia than conventionally housed mice with liver fibrosis, and unlike the conventional mice, the germ-free mice do not develop a neuroinflammatory response.…”
Section: Cirrhosis Spontaneous Bacterial Peritonitis Hepatic Encephmentioning
confidence: 99%
“…Therefore, 35 full-length articles were thoroughly reviewed, and 27 articles were further excluded as they did not report the outcome of interest. Finally, 3 cohort and 5 cross-sectional studies with a total of 40,295 participants met the eligibility criteria and were included in the metaanalysis [10][11][12][13][14][15][16][17]. Two of the 3 included cohort studies were published as conference abstracts [10,14].…”
Section: Resultsmentioning
confidence: 99%
“…The use of PPI may also lead to an increased risk of other types of organspecific bacterial infection. In fact, studies have suggested an increased risk of bacterial pneumonia among cirrhotic patients who use PPIs, although the results are inconsistent [10][11][12][13][14][15][16][17]. The current study aimed to further investigate this risk by identifying all available studies and summarizing their results together.…”
Section: Introductionmentioning
confidence: 99%